Induction of estrus using PGF 2alpha in non-descript hilly goats - SINGH, S K; RAM, HIRA; MEENA, H R; SHARMA, A K; RASOOL, T J (The Indian Journal of Animal Reproduction, 2023)
The present study was aimed to evaluate the efficacy of PGF :za injection on induction of estrus in 48 healthy hill goats. The PGF,. (Dinoprost tromethamine-7.5 mg/goats) was injected intramuscularly in half of the goats (n=24) and rest 24 goats were kept as control and they were exposed to buck only. The behavioural estrus was observed following buck parading twice only. The non-responders were injected with another similar dose of PGF24 10-11 days after the first one. The first and second PGF24 injection induced estrus in 9/24(37.5%) and 9/15(60%) goats, respectively with an .overall induction of estrus in 18/24 goats (75%) in comparison to only 5/24 (21%) goats in control. Most of the goats (11; 61.11%) exhibited estrus within 72 hours with an average of 108.22±27.39 and 95.77:1:22.26 hrs to first and second injection of PGF,., respectively. The goats observed in estrus were served to buck of high vigour on two occasions leading to pregnancy in 16/18 (88.88%) goats. The results indicated that PGF,. could be used effectively to induce estrus in hilly goats with high fertility.